An Innovative Method for the Production of Yoghurt Fortified with Walnut Oil Nanocapsules and Characteristics of Functional Properties in Relation to Conventional Yoghurts - Katarzyna Turek; Gohar Khachatryan; Karen Khachatryan; Magdalena Krystyjan (Foods, 2023)
Polyunsaturated fatty acids (PUFAs) are crucial nutrients involved in a plethora of metabolic and physiological processes. PUFAs have been extensively researched for their effects on human nutrition and health. The high demand for these fatty acids offers the possibility of adding vegetable oils to dairy products such as yoghurt. The aim of this study was to produce nano/microcapsules comprising walnut oil through exclusively natural ingredients utilised in yoghurt manufacturing. Additionally, the study tested yoghurt supplemented with PUFAs using the acquired nano/microcapsules. Chemical and physiochemical properties, microbiological analysis, rheological measurements, texture analysis, scanning electron microscope (SEM) analysis, ATR-FTIR spectroscopy, and sensory and fatty acids profile analysis were performed. A physico-chemical analysis highlighted the impact of oil addition on fat and dry matter concentration, revealing an increased quantity of said components in yoghurt after oil addition. Based on the identified parameters for potential and active acidity in the yoghurts, normal lactic fermentation was observed. Furthermore, the addition of oil was found to have an impact on the pH of the yoghurt. Microbiological analysis indicated that the incorporation of nano-encapsulated walnut oil did not have any notable effect on the abundance of determined microorganisms in the yoghurt. However, it was observed that the number of Lactobacillus delbrueckii ssp. bulgaricus increased as a result of storage. The incorporation of enclosed oil in yoghurt resulted in negligible alterations in rheological and sensory characteristics when compared with the plain variant. The addition of oil had an effect on most of the analysed fatty acids. Fortified yoghurt shows a more favourable proportion of the fatty acid groups tested (SFA, MUFA, and PUFA) and lower values of fat quality factors (AI and TI).